Long-term assessment of six-stacked scaled-up MFCs treating swine manure with different electrode materials. Issue 5 (1st August 2017) - Vilajeliu-Pons, A.; Puig, S.; Salcedo-Dávila, I.; Balaguer, M. D.; Colprim, J.
Abstract : Evaluation of different electrode materials in stacked scaled-up MFCs for swine manure treatment to move the technology towards application. Abstract : Microbial fuel cell (MFC) technology is a bio-approach to remove organic matter and nitrogen from wastewater with concomitant production of renewable electricity. Nowadays, there exists clear interest in moving MFCs towards application. This study aims to demonstrate the feasibility of MFC technology for treating swine manure. A couple of 6-stacked MFCs presenting a total volume of 115 L were designed and operated to treat swine manure at 50 L d −1 for more than 6 months. Two different electrodes were tested, one for each stacked MFC: granular graphite (GG-MFC) and stainless steel mesh (SS-MFC). Organic matter was oxidised in the anode compartments, ammonium was oxidized to nitrate in an external aerated reactor, and nitrate was reduced to dinitrogen gas in the biocathodes. GG and SS-MFCs reached similar organic matter and nitrogen removal rates (1.9 ± 0.3 kg COD m −3 d −1 ; 0.35 ± 0.02 kg N m −3 d −1 ) with power densities between 2–4 W m −3, the central units being the most electroactive. However, the GG-MFC performance declined over time due to electrode crushing and the clogging of granular graphite which reduced its applicability in comparison with stainless steel. The application of the stacked SS-MFC with a mixed electric circuit is a feasible strategy to maintain or even improve treatment efficiencies and power densities when scaling-up MFCs.